26.6k views
2 votes
4x + 3y = 26 3x - 2y=11

User Uflex
by
5.2k points

2 Answers

2 votes

Explanation:

Hey, there!!

Given,

4x + 3y = 26........(i)

3x -2y = 11............(ii)

Multiplying equation (i) by 2 and equation (ii) by 3 we get,

8x - 6y = 52

9x + 6y = 33

17x = 85 { cancelling 6y and -6y}.


x = (85)/(17)

Therefore, x= 5.

Now, putting the value of x is equation (i)

4x + 3y = 26

4×5 + 3y = 26

20 + 3y = 26

3y = 26 -20


y = (6)/(3)

Therefore, y = 2.

Hope it helps.....

User Rob Squires
by
4.8k points
1 vote

Answer:

x = 5

Explanation:

2 (4x + 3y = 26)

3 (3x - 2y = 11)

8x + 6y = 52

9x - 6y = 33 [the 6y and -6y cancel out]

17x = 85 [divide both sides by 17 to find x]

x = 5

User Candise
by
4.6k points